ANALISIS CACAT MENGGUNAKAN METODE FTA DAN FMEA PADA DEPARTEMEN BUFFING UNTUK MENURUNKAN JUMLAH UNIT CACAT (Studi Kasus : PT.BWB) - Vera Methalina Afma; Edi Sumarya; Nirwan Ambatoding (Universitas Riau Kepulauan, 2022)
The research was conducted to determine the factors - factors that cause defects in products, and provide corrective suggestions on how to improve the quality of the product Bracket SLM 315 which is currently still exceed the standards set for the maximum defect is 1% per month . The problem approach used is using Pareto diagram tools, then using the method Fault Tree Analysis (FTA) and methods Failure Mode and Analysis (FMEA) and 5W + 1H tools. From the results of data processing using Pareto diagrams, it is found that the dominant type of defect is defects under size, then the analysis uses the Fault Tree analysis method and the method Failure Mode And Effect Analysis which is the priority for improvement, namely the quality of the material. with the causes of the lack of inspections in materials raw parts and priority improvements based on the value of the RPN biggest that operator does not carry out inspection of goods raw part advance with a value of 336, the proposed improvements using 5W + 1H is Making special tools / pin to be used operator to check raw parts and own work